Methods of Social Work with Older People at Different Providers of Services for Older People in Croatia - Tomašević, Suzana (Ревија за социјална политика/Journal of Social Policy, 2024)
The demographic data from the last census (2021) in the Republic of Croatia show that the proportion of older people in the total population will increase, as already predicted. With a larger number of older people, the likelihood of needing help with activities of daily living in later stages of life increases, especially among the population of 80 years and older, which leads to an increase in the number of services for the older people. With the development of social services for older people, different methods and approaches are being developed to meet the needs of older people in the community in which they live. The aim of this paper is to examine whether there are methods for working with older people that are used by different service providers for older people in Croatia. The article presents the methods of social work used by various service providers for older people and how they are based on concepts of social work with older people. The study used a qualitative approach with the interview method and the data was processed using the qualitative analysis method. The study involved 12 people who work in institutions and associations that provide services for older people. The results show that different methods of social work are present in the practise of working with older people and that the concepts of social work with older people are represented by service providers in which older people actively participate in the design of activities and services.